Comparison of DTPA and MAG-3 Scintigraphies via Measurement of Differential Renal Function Based on DMSA Static Renal Scintigraphy - Demirel, B. B.; Balci, T. A.; Tasdemir, B.; Koc, P. Z. (Springer, 2010)
[Abstract Not Available]
23rd Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 09-13, 2010 -- Vienna, AUSTRIA